Standardization of a bone formation biomarker quantification using screen printed electrodes. Issue 7 (8th August 2016) - Lee, Jukyung; Bubar, Cameron T.; Busnaina, Ahmed; Shefelbine, Sandra J.; Lee, Heayeon
ABSTRACT: The development of a rapid and highly sensitive and specific biosensor for measuring biomarkers of bone turnover is very important to measure the effectiveness of pharmaceutical treatments and to gauge the extent of the bone formation process. In recent years, the electronic biosensor for bone turnover markers was chosen as a new developing method for monitoring patients with certain bone diseases such as osteoporosis because of its sensitivity and specificity. In this article, the rapid and highly sensitive immunosensor for the bone resorption biomarker detection was developed using disposable impedimetric immunosensors. To achieve this, the working surfaces of commercial Dropsens 220AT electrodes were modified in order to create a functional immunolayer that was specific to the binding of the bone formation marker, alkaline phosphatase (ALP). After creating an immunolayer, various concentrations of ALP were detected in phosphate buffered solution and diluted fetal bovine serum (FBS). Using electrochemical impedance spectroscopy we were able to differentiate between various concentrations of ALP. Measuring ALP with immunosensors by electrochemical impedance spectroscopy resulted in a limit of detection of 5 ng/mL in PBS and 10 ng/mL in FBS. It is very similar to the detection limit of standard enzyme linked immunosorbent assay kits and within the biological range of ALP in human serum.